The Origin and Evolution of Plant Flavonoid Metabolism - Yonekura-Sakakibara, Keiko; Higashi, Yasuhiro; Nakabayashi, Ryo (Frontiers in Plant Science, 2019)
During their evolution, plants have acquired the ability to produce a huge variety of compounds. Unlike the specialized metabolites that accumulate in limited numbers of species, flavonoids are widely distributed in the plant kingdom. Therefore, a detailed analysis of flavonoid metabolism in genomics and metabolomics is an ideal way to investigate how plants have developed their unique metabolic pathways during the process of evolution. More comprehensive and precise metabolite profiling integrated with genomic information are helpful to emerge unexpected gene functions and/or pathways. The distribution of flavonoids and their biosynthetic genes in the plant kingdom suggests that flavonoid biosynthetic pathways evolved through a series of steps. The enzymes that form the flavonoid scaffold structures probably first appeared by recruitment of enzymes from primary metabolic pathways, and later, enzymes that belong to superfamilies such as 2-oxoglutarate-dependent dioxygenase, cytochrome P450, and short-chain dehydrogenase/reductase modified and varied the structures. It is widely accepted that the first two enzymes in flavonoid biosynthesis, chalcone synthase, and chalcone isomerase, were derived from common ancestors with enzymes in lipid metabolism. Later enzymes acquired their function by gene duplication and the subsequent acquisition of new functions. In this review, we describe the recent progress in metabolomics technologies for flavonoids and the evolution of flavonoid skeleton biosynthetic enzymes to understand the complicate evolutionary traits of flavonoid metabolism in plant kingdom.